Infection, Sepsis and the Inflammatory Response: Mechanisms and Therapy - Lonsdale, Dagan O.; Shah, Reya V.; Lipman, Jeffrey (Frontiers in Medicine, 2020)
Sepsis secondary to bacterial infection remains a significant cause of morbidity and mortality globally. Recent decades have seen the evolution of international collaborations to improve care for these patients and identify areas for research. In this article we discuss the pathophysiology underlying the condition, review the current recommended management strategies, discuss areas of controversy and highlight the need for ongoing research, particularly in diagnostics.